Neural Processing Differences of Facial Emotions Between Human and Vehicles: Evidence From an Event-Related Potential Study - Liu, Zhuo; Du, Wenjun; Sun, Zhongrui; Hou, Guanhua; Wang, Zhuonan (Frontiers in Psychology, 2022)
Vehicle face is a crucial factor influencing consumers' purchase intention of fuel vehicles and electric vehicles. However, little empirical evidence has been provided on whether people process the vehicle face as a human face. Besides, are there any differences between fuel and electric vehicle faces? This study investigates the neural processing relationship among human facial emotions, fuel vehicle, and electric vehicle facial emotions. A 2 (emotional expression)×3 (face type) repeated measures experiment was conducted. EEG data were recorded and processed. Results showed that human faces share a similar neural processing mechanism during the latency of 100-300ms. Both human and vehicle faces elicited ERP components of N170, EPN, and P2. Larger EPN and P2 suggested that fuel vehicle facial emotion can be perceived more efficiently than electric vehicles. These findings provide insight for vehicle designers to better understand the facial emotions of cars.